Estufas climatizadas para experimentos ambientais com rãs, em gaiolas - Figueiredo, Mario Roberto Chim; Lima, Samuel Lopes; Agostinho, Claudio Angelo [UNESP]; Baêta, Fernando da Costa; Weigert, Stefan Cruz (Sociedade Brasileira de Zootecnia, 2001)
Foram construídas seis estufas climatizadas, instaladas inicialmente no Ranário Experimental da Universidade Federal de Viçosa (UFV) e, posteriormente, no Ranário Experimental da Fundação Universidade Federal do Rio Grande, com o objetivo de realizar experimentos para avaliar os efeitos do ambiente sobre o desempenho de rãs em gaiolas de fibra de vidro. Ambientes com temperaturas de 25ºC e fotoperíodo de 12/12 horas de luz/horas de escuridão (h L/E) serviram para adaptação das rãs por 15 dias antes de cada experimento. Os tratamentos consistiram em simular ambientes com temperaturas variando de 20 a 35ºC e fotoperíodos de 8/16, 12/12 e 16/8 h L/E. Foram realizados experimentos com rã-touro (Rana catesbeiana Shaw, 1802) e rã-manteiga (Leptodactylus ocellatus Linnaeus, 1758). Nessas estufas foi possível estimar que: a) os maiores ganhos de peso de rã-touro foram obtidos entre 27,6 e 29,7ºC, com melhor crescimento entre 28,2 e 30,1ºC; para rã-manteiga os melhores ganhos e conversão alimentar foram observados a 28,6 e 28ºC, respectivamente; b) a temperatura interage com fotoperíodo sobre o desempenho das rãs e seu desenvolvimento gonadal; c) a 27,7ºC (temperatura de conforto térmico) haverá menos rãs dentro d'água; d) a maior temperatura cloacal de rã-touro, 32,1ºC no seco e 33,8ºC dentro d'água, a 35ºC, evidenciou que as rãs se termorregulam; e) os níveis de tetraiodotironina (T4) no plasma decrescem na temperatura de conforto térmico; f) rã-manteiga condiciona-se ao manejo de rotina, reunindo-se ao redor do cocho na hora da alimentação.

Six acclimatized incubators were initially installed in the Experimental Frog Farm of the Federal University of Viçosa and later in Experimental Frog Farm of the Federal University of Rio Grande, with the objective of accomplishing experiments to evaluate the effects of the environment on frogs performance in cages of fiber glass. Environments with temperatures of 25ºC and photoperiod of 12/12 hours of light/hours of darkness (h L/D) were available to frogs adaptation during 15 days before each experiment. The treatments consisted to simulate environments with temperatures varying from 20 to 35ºC and photoperiods of 8/16, 12/12 and 16/8 h L/D. They were accomplished experiments with bullfrog (Rana catesbeiana Shaw, 1802) and with butterfrog (Leptodactylus ocellatus Linnaeus, 1758). In these incubators it was possible to estimate that: a) the highest weight gain of bullfrog was obtained between 27.6 and 29.7ºC, with better growth between 28.2 and 30.1ºC; for butterfrog the best gain and alimentary conversion were verified at 28.6 and 28ºC, respectively; b) temperature interact with photoperiod affecting the frogs performance and gonadal development; c) at 27.7ºC (temperature of thermal comfort) there will be less frogs inside of water; d) the highest cloacal temperature: 32.1ºC, in the dry part, and 33.8ºC, inside of water, at 35ºC, evidenced the bullfrog thermoregulation; e) the tetraiodotironine (T4) level in the plasm decreases in the temperature of thermal comfort; f) butterfrog was conditioned to the routine handling, coming around feeder at eater time.
Acclimatized incubators for environmental experiments with frogs, in cages
Keywords: ambiente; desempenho; desenvolvimento gonadal; estufas; fotoperíodo; gaiolas; rã-manteiga; rã-touro; temperatura; bullfrog; butterfrog; cages; environment; gonadal development; incubators; performance; photoperiod; temperature